Integrasi Sistem Fotovoltaik Dalam Rancangan Bangunan Bertingkat Rendah Guna Meningkatkan Kinerja Energi - A’yun, Qurrotul; Heryanti, Septia (Nature: National Academic Journal of Architecture, 2024)
The significant problem of greenhouse gas emissions from the building sector, contributes more than a third of global emissions and around 40% of world energy consumption. One solution offered to overcome this problem is the integration of photovoltaic systems in building design. Photovoltaic technology allows the conversion of solar energy into electricity, thereby reducing dependence on non-renewable energy and minimizing CO₂ emissions. This study was conducted using an experimental method, in the form of direct testing, to assess the performance of a monocrystalline photovoltaic system, which was integrated into buildings with various orientations and tilt angles. The research was conducted in Surabaya, as one of the cities with high intensity of sunlight in a tropical climate area, by testing photovoltaic panels installed in five positions, namely on the roof, and the facades on the north, east, south, and west sides. Data were collected by measuring voltage, current, power, temperature, and sunlight intensity during the irradiation period between 07.00 and 17.00 WIB. The main variables tested were irradiation time, orientation of the direction of the face, and the tilt angle of the panel. The results showed that the roof position and the north facade are the most optimal for photovoltaic operation, with the highest power production of around 120 Watts for the roof position and 110 Watts for the north facade. The east side produces optimal power in the morning, while the west side is more efficient in the afternoon. The slope angles of 30° and 45° proved to be the most effective for producing maximum power. The aesthetic integration of the facade with a slope of 60° is also considered to provide good visual value for the building. This study provides specific recommendations regarding the optimal orientation, operating time, and slope angle configuration to maximize the energy performance of the photovoltaic system in tropical building designs.